Meripilus giganteus ethanolic extract exhibits pro-apoptotic and anti-proliferative effects in leukemic cell lines - Monia Lenzi; Veronica Cocchi; Aleksandra Novaković; Maja Karaman; Marijana Sakač; Anamarija Mandić; Milica Pojić; Maria Cristina Barbalace; Cristina Angeloni; Patrizia Hrelia; Marco Malaguti; Silvana Hrelia (BMC, 2018)
Abstract Background The interest towards botanicals and plant extracts has strongly risen due to their numerous biological effects and ability to counteract chronic diseases development. Among these effects, chemoprevention which represents the possibility to counteract the cancerogenetic process is one of the most studied. The extracts of mushroom Meripilus giganteus (MG) (Phylum of Basidiomycota) showed to exert antimicrobic, antioxidant and antiproliferative effects. Therefore, since its effect in leukemic cell lines has not been previously evaluated, we studied its potential chemopreventive effect in Jurkat and HL-60 cell lines. Methods MG ethanolic extract was characterized for its antioxidant activity and scavenging effect against different radical species. Moreover, its phenolic profile was evaluated by HPLC-MS-MS analyses. Flow cytometry (FCM) analyses of Jurkat and HL-60 cells treated with MG extract (0-750 μg/mL) for 24-72 h- allowed to evaluate its cytotoxicity, pro-apoptotic and anti-proliferative effect. To better characterize MG pro-apoptotic mechanism ROS intracellular level and the gene expression level of FAS, BAX and BCL2 were also evaluated. Moreover, to assess MG extract selectivity towards cancer cells, its cytotoxicity was also evaluated in human peripheral blood lymphocytes (PBL). Results MG extract induced apoptosis in Jurkat and HL-60 cells in a dose- and time- dependent manner by increasing BAX/BCL2 ratio, reducing ROS intracellular level and inducing FAS gene expression level. In fact, reduced ROS level is known to be related to the activation of apoptosis in leukemic cells by the involvement of death receptors. MG extract also induced cell-cycle arrest in HL-60 cells. Moreover, IC50 at 24 h treatment resulted 2 times higher in PBL than in leukemic cell lines. Conclusions Our data suggest that MG extract might be considered a promising and partially selective chemopreventive agent since it is able to modulate different mechanisms in transformed cells at concentrations lower than in non-transformed ones.